1997
DOI: 10.1007/s004380050541
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei sequences that bind to the nuclear matrix enhance transformation frequency

Abstract: Three DNA fragments, trs1, 2 and 3, were isolated from the Trichoderma reesei genome on the basis of their ability to promote autonomous replication of plasmids in Saccharomyces cerevisiae. Each trs element bound specifically to the isolated T. reesei nuclear matrix in vitro, and two of them bound in vivo, indicating that they are matrix attachment regions (MARs). A similar sequence previously isolated from Aspergillus nidulans (ans1) was also shown to bind specifically to the T. reesei nuclear matrix in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Interestingly, it was reported that three Trichoderma reesei MARs enhanced the frequency of integrative transformation of T. reesei up to five‐fold (Belshaw et al 1997). A tobacco MAR flanking the gusA reporter gene increased the frequency of kanamycin‐resistant poplar shoots (Han et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was reported that three Trichoderma reesei MARs enhanced the frequency of integrative transformation of T. reesei up to five‐fold (Belshaw et al 1997). A tobacco MAR flanking the gusA reporter gene increased the frequency of kanamycin‐resistant poplar shoots (Han et al 1997).…”
Section: Introductionmentioning
confidence: 99%